2018
DOI: 10.1016/s2213-8587(18)30079-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific relevance of diabetes to occlusive vascular and other mortality: a collaborative meta-analysis of individual data from 980 793 adults from 68 prospective studies

Abstract: SummaryBackgroundSeveral studies have shown that diabetes confers a higher relative risk of vascular mortality among women than among men, but whether this increased relative risk in women exists across age groups and within defined levels of other risk factors is uncertain. We aimed to determine whether differences in established risk factors, such as blood pressure, BMI, smoking, and cholesterol, explain the higher relative risks of vascular mortality among women than among men.MethodsIn our meta-analysis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(90 citation statements)
references
References 34 publications
7
81
0
2
Order By: Relevance
“…Several reports have demonstrated increased relative risk of vascular mortality in women with diabetes compared with men, although the precise mechanism is not known . Our data, with lower levels of TFPI accompanied by increased F1+2 in females with type 1 diabetes, support a prothrombotic milieu, which might lead to vascular disease.…”
Section: Discussionsupporting
confidence: 56%
“…Several reports have demonstrated increased relative risk of vascular mortality in women with diabetes compared with men, although the precise mechanism is not known . Our data, with lower levels of TFPI accompanied by increased F1+2 in females with type 1 diabetes, support a prothrombotic milieu, which might lead to vascular disease.…”
Section: Discussionsupporting
confidence: 56%
“…Sex differences in CVD outcomes for adults with type 2 diabetes across the life span Type 2 diabetes is a significant risk factor for CVD for both women and men. Findings from large-scale consortia of cohort studies have shown that the presence of diabetes doubles the risk of having a myocardial infarction or stroke [14,15,72]. However, as with other major vascular risk factors, such as blood pressure and BMI, the strength of the association between diabetes and vascular outcomes diminishes with age, partly because of the lower baseline risk for CVD in younger as compared with older adults [72,73].…”
Section: Sex Differences In Type 2 Diabetes Prevalence In Midlife Andmentioning
confidence: 99%
“…Findings from large-scale consortia of cohort studies have shown that the presence of diabetes doubles the risk of having a myocardial infarction or stroke [14,15,72]. However, as with other major vascular risk factors, such as blood pressure and BMI, the strength of the association between diabetes and vascular outcomes diminishes with age, partly because of the lower baseline risk for CVD in younger as compared with older adults [72,73]. For example, in the largest meta-analysis to date, the rate ratio (RR) of occlusive vascular death was found to be greatest in men and women aged 35 ; p = 0.0001 for trend across age groups) [72].…”
Section: Sex Differences In Type 2 Diabetes Prevalence In Midlife Andmentioning
confidence: 99%
“…A recent meta-analysis evaluating the role of diabetes in PAD has shown that diabetes, independently from other major vascular risk factors, substantially increases vascular risk in both men and women [2]. However, lifestyle changes to reduce smoking and obesity and use of cost-effective drugs that target major vascular risks (including statins and antihypertensive drugs) – while remaining important in both men and women with diabetes – might not reduce the relative excess risk of occlusive vascular disease in women with diabetes [2].…”
Section: Is Diabetes a Coronary Risk Equivalent?mentioning
confidence: 99%
“…However, lifestyle changes to reduce smoking and obesity and use of cost-effective drugs that target major vascular risks (including statins and antihypertensive drugs) – while remaining important in both men and women with diabetes – might not reduce the relative excess risk of occlusive vascular disease in women with diabetes [2]. Hence, in such a controversial field, gender-related differences could play a fundamental role [13].…”
Section: Is Diabetes a Coronary Risk Equivalent?mentioning
confidence: 99%